The effectiveness of the free nutritious food program in increasing students' enthusiasm and interest in learning at school - Zuliana Amalia; Nabila Lisa Azahra; Nia Felisa (Lembaga Riset Mutiara Akbar, 2025)
The Makan Bergizi Gratis (MBG) is a strategic policy of the Indonesian government launched in 2025 with the aim of improving the nutritional status and quality of students' education. Learning interest, a crucial factor in educational success, is strongly influenced by students' physiological condition, motivation, and readiness to learn, which are closely related to daily nutritional needs. Numerous studies over the past decade have shown that nutritious school meal programs positively contribute to student attendance, engagement, and academic achievement, although the magnitude of the impact varies. Furthermore, recent research confirms that food insecurity is negatively associated with children's learning motivation, suggesting that programs such as the MBG could be a solution to increase learning interest by reducing nutritional and food barriers. The MBG program has significant potential to increase student learning interest through nutrition, motivation, and socioeconomic factors. However, direct empirical evidence on learning interest remains limited. Therefore, field research that directly measures indicators of learning interest (e.g., engagement, intrinsic motivation, and enjoyment of learning) is essential to evaluate the program's effectiveness.